Implementation of Think Pair Share Model Assisted by E-Cergam Media to Improve Critical Thinking Ability of Elementary School Students - Zuhrotul Isnaini; Much Arsyad Fardani; Ika Ari Pratiwi (Universitas Negeri Semarang, 2025)
Background – The low critical thinking skills in Pancasila Education limit students’ ability to analyze information, argue logically, and present clear arguments. Research Urgency – Developing critical thinking skills requires learning models that facilitate active discussions and use contextual media, enabling students to better understand the material and enhance higher-order thinking skills. Research Objectives – This study aimed to examine the improvement of students’ critical thinking skills in Pancasila Education before and after implementing the Think Pair Share (TPS) model assisted by e-cergam media. Research Method – The research used a quantitative approach with a pre-experimental one-group pretest-posttest design. Participants were 23 fifth-grade students of SDN 1 Sidorekso in the 2024/2025 academic year, selected through saturated sampling. The instruments consisted of 15 pretest and posttest questions covering FRISCO indicators, and data were analyzed using N-Gain test. Research Findings – The results showed a medium increase (N-Gain = 0.4874), with the average score increasing from 52.74 to 75.74, a gain of 23 points. All indicators increased, with clarity showing the highest gain (N-Gain 0.724). The Pair stage in TPS model has proven to be the most effective in encouraging active group discussions, while e-cergam media provided contextual stories and tasks aligned with critical thinking indicators, which were found to gradually develop students’ critical thinking skills. Conclution - The Think Pair Share model assisted by e-cergam media effectively improved students’ critical thinking skills in Pancasila Education. Research Novelty/Contribution – The novelty of this study lies in integrating the TPS model with contextual-based e-cergam media in Pancasila Education, which has not widely studied before. This combination supports the development of students’ critical thinking skills through active group discussions and contextual storytelling.